Peran Training Dan Coaching Dalam Pengembangan Kinerja Karyawan Perusahaan Padat Karya - Abdul Kadir; Norlaily Maulida (Islamic University of Kalimantan MAB Banjarmasin, 2023)
This review plans to test: (1) know the expected set of responsibilities of Work Preparing (Training) and representative execution at PT. Surya Satria Timur Banjarmasin, (2) realizing that Occupation Preparing (Training) affects representative execution at PT. Surya Satria Timur Banjarmasin. The plan of this study is a quantitative report and is an overview study, where information is gotten from a poll. The review test is 43 representatives of PT. Surya Satria Timur Banjarmasin with basic straight regresie information examination. The consequences of the review show that: 1) There is a halfway impact of Occupation Preparing (Training) on representative execution at PT. Surya Satria Timur Banjarmasin (0.000 < 0.05). 2) There is a semi-persuasive impact on worker execution at PT. Surya Satria Timur Banjarmasin Area, Tanah Bumbu Rule (0.000 < 0.05). 3) There is a concurrent impact of Occupation Preparing (Training) and work inspiration on representative execution at PT. Surya Satria Timur Banjarmasin (0.000 < 0.05). An idea that can be recommended is the need to normalize and facilitate the time of Occupation Preparing (Training) to the capacity of the labor force to get Work Preparing (Training) materials, ideally great representatives are given Work Preparing (Training) and inspiration through advancements and motivators so they can work on their inspiration and execution.